2016
DOI: 10.1002/ptr.5728
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Multiple‐Dose Treatment with Baicalein on the Pharmacokinetics of Ciprofloxacin in Rats

Abstract: Ciprofloxacin is used as a treatment for urinary and respiratory tract infections in clinical practice. Baicalein, a major flavonoid present in Scutellaria baicalensis, is a well-known and potent antibacterial compound used in complementary and alternative medicine practices. The present study aimed to clarify the effects of multiple-dose treatment with baicalein on the pharmacokinetics of ciprofloxacin in rats. Following the oral administration of baicalein (20, 40, or 80 mg/kg) for five consecutive days, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, the bioavailability of CPFX after oral administration is reported to be 20% in rats, 33) while, bioavailability in humans is 69%. 34) In addition, the elimination half-life in the rat is 1.55 h, 33) compared to 4.11 h in humans. 34) Therefore, considering these differences between rats and humans, the dose of CPFX was set at 20 mg/kg for rats, which is 5-fold higher than that of humans, to ensure the C max would be approximately the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bioavailability of CPFX after oral administration is reported to be 20% in rats, 33) while, bioavailability in humans is 69%. 34) In addition, the elimination half-life in the rat is 1.55 h, 33) compared to 4.11 h in humans. 34) Therefore, considering these differences between rats and humans, the dose of CPFX was set at 20 mg/kg for rats, which is 5-fold higher than that of humans, to ensure the C max would be approximately the same.…”
Section: Discussionmentioning
confidence: 99%
“…34) In addition, the elimination half-life in the rat is 1.55 h, 33) compared to 4.11 h in humans. 34) Therefore, considering these differences between rats and humans, the dose of CPFX was set at 20 mg/kg for rats, which is 5-fold higher than that of humans, to ensure the C max would be approximately the same. Accordingly, thylakoid-rich spinach extract was administered at 500 mg/kg to keep the dose ratio of 1 : 25.…”
Section: Discussionmentioning
confidence: 99%
“…PAH model was induced by intraperitoneal injection of 50 mg/kg of monocrotaline (MCT) for 6 weeks (Sigma‐Aldrich) as per our previously described with modifications 16 . Blood samples were collected at specific time points, the plasma concentration was determined, 18 and we choose the drug concentration according to the report 15 . In the present study, we have tested the lower dose (20 mg/kg, 50 mg/kg) and higher dose (200 mg/kg), the most effective dose is 100 mg/kg, and the main purpose of this present study is to explore the mechanism, so we only choose 100 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that inflammatory mediator tumor necrosis factor-α (TNF-α) can further promote the development of PAH by reducing BMPR2 expression in PASMCs [Yang et al, 2017]. Our previous studies have shown that baicalin could inhibit inflammation and improve PAH vascular remodeling by reducing TNF-α factor expression and regulation of BMPR2 signaling pathways in MCT-induced PAH rats, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, there few literatures have been reported about the pharmacokinetic studies of ZgI during the past 20 years [9]. Recently years, a large number of studies have demonstrated that pharmacokinetics of drugs can be affected by many factors, including age, gender, altitude, drugs and variety of diseases, such as diabetes, Hypertension, estrogen level and so on [10][11][12][13][14][15][16][17]. Actually, drugs are used to treat diseases, and the patients are the ultimate consumers of drugs [18].…”
Section: Introductionmentioning
confidence: 99%